2001
DOI: 10.1152/ajplung.2001.281.4.l766
|View full text |Cite
|
Sign up to set email alerts
|

Functional components of basic fibroblast growth factor signaling that inhibit lung elastin gene expression

Abstract: Previously, we have demonstrated that basic fibroblast growth factor (bFGF) decreases elastin gene transcription in confluent rat lung fibroblasts via the binding of a Fra-1-c-Jun heterodimer to an activator protein-1-cAMP response element in the distal region of the elastin promoter. In the present study, we show that bFGF activates the mitogen-activated protein kinase extracellular signal-regulated kinase 1/2, resulting in the translocation of phosphorylated extracellular signal-regulated kinase 1/2 into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
30
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 36 publications
4
30
1
Order By: Relevance
“…We first established that elastase treatment of matrix-laden pulmonary fibroblast cultures resulted in a detectable amount of soluble HB-EGF within the elastase-released products. Addition of soluble HB-EGF to undigested fibroblast cultures decreased the steady-state level of elastin mRNA through a mechanism similar to that reported for FGF-2 (6,42). Furthermore, we show that HB-EGF treatment of pulmonary fibroblasts leads to an increase in endogenous FGF-2 mRNA and protein levels.…”
supporting
confidence: 80%
“…We first established that elastase treatment of matrix-laden pulmonary fibroblast cultures resulted in a detectable amount of soluble HB-EGF within the elastase-released products. Addition of soluble HB-EGF to undigested fibroblast cultures decreased the steady-state level of elastin mRNA through a mechanism similar to that reported for FGF-2 (6,42). Furthermore, we show that HB-EGF treatment of pulmonary fibroblasts leads to an increase in endogenous FGF-2 mRNA and protein levels.…”
supporting
confidence: 80%
“…6,14,15 Thus, inhibition of its phosphorylation seems to be a promising strategy to regulate elastin synthesis in models deficient in elastin content. Using aortic vSMCs isolated from the BN rat, an inbred strain deficient in elastin synthesis, we demonstrated that inhibition of ERK1/2 phosphorylation by U0126, an inhibitor of MEK1/2 activity, increases elastin gene transcription.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 The mechanism most studied is probably the decreased elastin gene transcription by bFGF in human vSMCs 10 and rat pulmonary fibroblasts. [11][12][13][14] EGF and bFGF were shown to decrease elastin gene transcription by activating extracellular signalregulated kinases 1/2 (ERK1/2), resulting in its translocation to the nucleus and subsequent induction of c-fos and fra1. 10,[13][14][15] Heterodimers c-fos/c-jun and fra1/c-jun form the activator protein-1 (AP1) complex that represses elastin gene transcription through its binding to an AP1/cAMP response element-like sequence located on the human elastin gene.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Carreras et al demonstrated that bFGF-mediated activation of the MAPKElk-1 pathway plays a pivotal role in the transcriptional repression of the ECM component elastin in lung fibroblasts (Carreras et al, 2001). Similarly, in human articular chondrocytes, the stimulation of multiple MAPK pathways subsequently activates the downstream transcription factor Elk-1, which then translocates into the nucleus and stimulates MMP-13 gene expression through protein-DNA interaction (Figure 2) .…”
Section: (C) Extracellular Signaling Mediated By Bfgfmentioning
confidence: 98%